Pułapka „ciepłych portretów”. Wybrane przykłady ukraińskich heteroobrazów w literaturze i kinie polskim na początku XXI wieku - Kupidura, Ryszard (Studia Ukrainica Posnaniensia, 2023)
The expressions of Polish solidarity with Ukrainians after the aggression of the Russian Federation on February 24, 2022 was absolutely unprecedented. Undoubtedly, such a radical historical breakthrough would not have been possible without the contribution of Ukrainian migration diplomacy, implemented, often unknowingly, by hundreds of thousands of migrants who, through direct contact with Poles, reduced the conflict-causing potential of Ukrainian-Polish history. The aim of this paper is to examine the evolution of Ukrainian heteroimages appearing in Polish cinema and literature at the beginning of the 21st century, e.g. Lady from Ukraine by Paweł Łoziński, Ukrainian girl by Barbara Kosmowska and reportages written by Marta Mazuś and Monika Sobień-Górska. The author also focuses attention on the migration counter-discourse in Guest Worker Literature, the role of the Polish-Ukrainian theater and the intercultural perspective for future literary and artistic searches.